Penerapan Media Edukasi dalam Meningkatkan Kesadaran dan Kesiapsiagaan Menghadapi Kegawatdaruratan Medis - Rio Herwanto; Sentot Imam Suprapto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Medical emergencies require rapid, accurate, and coordinated responses to prevent disability and mortality. Family members in the Emergency Department (ED) hold a crucial role as potential first responders within the chain of survival; however, their level of knowledge and preparedness is often inadequate. Objective: This emergency nursing residency project aimed to enhance the awareness and preparedness of patient families in responding to medical emergencies through a strucred educational intervention at RS Dik Pusdikkes Puskesad Jakarta in 2025. Method: A pre-post educational intervention design wa employed with a total of 120 ED patient family members, selected through lectures, instructional videos, and demonstrations of Basic Life Support (BLS), recovery position, and activation of the 119 emergency system. Data were collected using pre-post test tests and a preparedness questionnaire. Analysis included descriptive statistics and problem mapping using Fishbone, USG (Urgency-Seriousness-Growth), and SWOT. Result: Pre-test results indicated low baseline knowledge, with an average score of 42.5%, particularly in BLS (37%), recovery position (32%), and activation of the 119 emergency service (40%). Following the intervention, knowledge significantly increased to 86.3% (an improvement of 43.8%). The greatest improvement was observed in the activation of 119 (+51%) and the recovery position (+50%). Additionally, 87% of participants reported increased confidence in responding to emergencies, and 98% expressed high satisfaction with the program. Conclusion: The educational intervention effectively improved the knowledge, preparedness, and emergency response capability of patient families. This program is recommended to be implemented as a routine ED activity supported by standardized operating procedures, digital learning media, and facilitator training for ED nurses. These findings highlight that empowering patient families can contribute significantly to patient safety and srengthening hospital emergency system.